Passiflora quadrangularis L. prevents experimental hypertension and vascular remodelling in rats exposed to nitric oxide deficit - BAREÑO, Lesly L.; PUEBLA, Pilar; GUERRA, Carlos M.; SAN FELICIANO, Arturo; ISAZA, Gustavo; GUERRERO, Mario F. (Vitae, 2017)
Background: Passiflora quadrangularis L. is among the species used in Colombian folk medicine for hypertension, but until now it has not been studied in experimental models. Objectives: To assess the capacity of P. quadrangularis L. EtOH extract to prevent the hypertension and vascular remodelling induced by nitric oxide (NO) deficit in Wistar rats. Methods: The nitric oxide (NO) synthase inhibitor L-NAME (10 mg/kg, i.p (intraperitoneal), every 48h) was administered for seven weeks to the following groups of rats: P. quadrangularis L.75, 150 and 300 mg/kg/d, p.o. (oral route); enalapril as reference agent, 10 mg/kg/d, p.o. and vehicle as control (mixture of propylene glycol 10%, glycerine 10% and polysorbate 2%). Arterial blood pressure (BP) and heart rate (HR) were measured twice a week. After sacrifice, the aortic rings were isolated, contraction was triggered with phenylephrine (PE 10-6 M) and then the relaxant response achieved with cumulative concentrations of acetylcholine (ACh, 10-10 – 10-5 M) or sodium nitroprusside (SNP, 10-10 – 10-5 M) was assessed. Histopathologic measures of thickness/lumen ratio from both the left ventricle and aorta walls, as well as phytochemical screening, were also performed. Results: As for enalapril, all doses of P. quadrangularis L. prevented the hypertension induced by L-NAME (122±1.2 versus 155±1.3 mmHg at seventh week). P. quadrangularis L. significantly increased the relaxant effect induced by ACh in isolated aorta and decreased the thickness/lumen ratio of aorta wall specimens. Conclusions: P. quadrangularis L. prevents experimental hypertension induced in rats with nitric oxide deficits improving the endothelium vasodilatation response and protecting against vascular remodelling.